Congenital Generalized Lipodystrophy: A Multisystemic Metabolic Disorder - Vishal V Tewari; Ritu Mehta; Kunal Tewari (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2016)
Introduction: Congenital generalized lipodystrophy or Berardinelli-Seip syndrome is a rare autosomal recessive multisystem disorder characterized by the near absence of  ubcutaneous and visceral adipose tissue from birth or early infancy with severe insulin resistance. It is caused by mutations in the gene for AGPAT-2 on chromosome 9 or BSCL-2/Seipin on chromosome 11 resulting in triglyceride-depleted adipocytes. BSCL-2/Seipin is a cell autonomous regulator of lipolysis essential for adipocyte differentiation.  Case: A 6-year-old male child presented with abdominal distention. He was noted to have a characteristic phenotype with generalized absence of subcutaneous fat over the body with acanthosis nigricans and hepatomegaly. His anthropometric indices were above the 75th centile for age and he was in sexual maturity rating Stage II. Investigations revealed hyperglycemia, hypercholesterolemia with fatty infiltration of liver and hyperinsulinemia with normal Growth hormone levels and accelerated bone age. The clinical features, pathogenesis, management and prognosis are discussed.  Conclusion: Congenital   eneralized lipodystrophy is an exceptionally rare disorder with prevalence of 1 per 12 million  opulation, affecting all ethnic groups. It is characterized by generalized lipodystrophy, acanthosis nigricans, prominent superficial veins, muscle hypertrophy, hirsuitism, accelerated skeletal growth with tall stature and genital precocity. Metabolic derangements seen are hyperlipidemia, hepatomegaly and non-ketotic insulin resistant diabetes mellitus. Death occurs in the third decade due to complications of diabetes, cardiomyopathy or cirrhosis. Our case showed all the phenotypic and metabolic features of this syndrome with early appearance of and difficult to control diabetes mellitus.